Drug use and its correlates in an Australian prisoner population - Butler, Tony; Levy, M.; Dolan, K.; Kaldor, J. (Harvard Academic Publishers, 2003)
The prevalence of past and present tobacco, alcohol, and illicit drug use is examined in a cross sectional random sample of prisoners. 789 male and female prisoners from 27 correctional centres across New South Wales (NSW) participated in the survey. Information was collected using a face-to-face interview on community and prison drug use, and intoxication while offending. Current tobacco use was reported by 72% of the sample. Use of alcohol by females was more likely than males to be classified as ‘safe’ according to the Alcohol Use Disorders Identification Test (39 vs. 26%). Overall, 64% of prisoners had used illicit drugs at some time in the past with cannabis and heroin the most common. Forty four percent of prisoners had a history of injecting drug use, with injecting prevalence significantly higher in females than males (64 vs. 40%) with approximately half of both male and female injectors reporting that they had injected while in prison. ‘Harmful’ or ‘hazardous’ use of alcohol was associated with imprisonment for violent crimes. Sixty two percent of property offenders had an injecting history. Correctional authorities need to ensure that drug treatment programmes are available to prisoners and consideration should be given to piloting needle and syringe exchange programmes in NSW prisons given the high levels of sharing injecting equipment in prison.